Climate-related soil saturation and peatland development may have conditioned surface water brownification at a central European lake for millennia - Tichá, Anna; Vondrák, Daniel; Moravcová, Alice; Chiverrell, Richard; Kuneš, Petr (The Science of the total environment, 2023)
Water brownification has long altered freshwater ecosystems across the northern hemisphere. The intensive surface water brownification of the last 30 years was however preceded by previous long-lasting more humic browning episodes in many catchments. To disentangle a cascade of browning-induced environmental stressors this longer temporal perspective is essential and can be reconstructed using paleolimnological investigations. Here we present a Holocene duration multi-proxy paleolimnological record from a small forest mountain lake in the Bohemian Forest (Czechia) and show that climate-related soil saturation and peatland development has driven surface water brownification for millennia there. A long core retrieved from the central part of the lake was dated using 14C and 210Pb, subsampled and analyzed for diatoms and zoological indicator (chironomids, planktonic cladocerans) remains. X-ray fluorescence (XRF) provided a record of elements sensitive to biogeochemical processes connected to browning and catchment development (P, Ti, Al/Rb, Fe/Ti, Mn/Ti, Si/Ti). Three threshold shifts related to the processes of water browning were detected in both diatom and chironomid successions at ~10.7, ~5.5 and ~4.2 cal. ky BP. Since, postglacial afforestation of the catchment ~10.7 cal. ky BP the lake experienced strong thermal stratification of the waters, but after ~6.8 cal. ky BP soil saturation and expansion of peatlands led to effective shading and probable nutrient limitation within the lake ecosystem. The more intensive in-wash of dissolved organic matter appears to decline after ~4.2 cal. ky BP, when the paludified catchment soils became permanently anoxic. Two temporary negative and positive anomalies of browning progress occur at the same time and may be connected with the "8.2 ka event" and the "4.2 ka event", respectively. The key role of peatlands presence in the catchment was manifested in millennial-scaled browning process and a climatic forcing of long-lasting browning is evidenced by coincidence with the moistening of climate across the northern hemisphere after ~6 cal. ky BP.
Keywords: voda; ekosystém; Natural acidification; Paludification; Humic substances; půda; Bohemian Forest; Dystrophication; Mid-Holocene climate transition; Ecosystem; Water; Soil